Fundamentals of fingerprint analysis - Daluz, Hillary Moses (Boca Raton, Florida : CRC Press, Taylor & Francis Group, 2015)
'Preface Due to the'CSI effect', interest in the forensic sub-disciplines has burgeoned. Consequently, hundreds of forensic science programs have arisen in universities around the world over the past decade. While dozens of professional fingerprint texts are available few, if any, are intended for students. Fundamentals of Fingerprint Analysis incorporates not only professional topics and technologies, but also the background and basic science behind these subjects. A majority of forensic sub-disciplines utilize some form of fingerprint analysis. Understanding the fundamentals of fingerprint analysis prepares the student for a career in the forensic sciences. Wherever possible, the most current research and advances in the science of fingerprint analysis are presented. This text is therefore also applicable to criminal justice professionals, attorneys, and laypersons that want to learn more about forensics. The laboratory manual entitled Fingerprint Analysis Laboratory Workbook is intended to accompany and enhance the topics addressed in the textbook. The book chapters align with the laboratory exercises. The laboratory exercises, introductory material, and post lab questions give students hands-on experience and supplemental information. Hands-on exercises enhance comprehension and enjoyment.'--
Preface -- Acknowledgments -- Author -- Section 1: Introduction To Fingerprints: -- Introduction: -- Key Terms -- Learning Objectives: -- Evolutionary development of friction ridges -- Introduction to forensic science -- Fingerprints as forensic evidence -- Finger print analysis -- Uniqueness and permanence -- Chapter summary -- Review questions -- References -- History: -- Key Terms -- Learning Objectives: -- Why study history? -- Ancient history -- Fingerprint science: seventeenth-nineteenth centuries -- Criminal records and classification -- Twentieth century -- I Had A Case: Applying fingerprint technology to archaeological research -- Chapter summary -- Review questions -- References -- Physiology And Embryology: -- Key Terms -- Learning Objectives: -- Biological uniqueness -- Layers of the skin -- Embryological development of friction ridges -- Embryological development of minutiae -- Permanence -- Chapter summary -- Review questions -- References -- Fingerprint Patterns And Classification: -- Key Terms -- Learning Objectives: -- Fingerprint patterns -- Loops -- Whorls -- Arches -- Fingerprint classification -- Henry classification -- NCIC classification -- Chapter summary -- Review questions -- References -- Known Fingerprints: -- Key Terms -- Learning Objectives: -- Known fingerprints -- Inked fingerprints records -- Powdered fingerprint records -- Digital fingerprint records -- Fingerprints from deceased individuals -- Chapter summary -- Review questions -- References -- Nature Of Latent Fingerprints: -- Key Terms -- Learning Objectives: -- Latent fingerprints -- Matrix -- Substrate -- Aging latent prints -- DNA from fingerprints -- I Had A Case: Aging latent fingerprints -- Chapter summary -- Review questions -- References -- Biometrics: Live-Scan And AFIS: -- Key Terms -- Learning Objectives: -- Biometrics -- Live-scan -- History of AFIS -- Ten-print searches -- Latent print searches -- Future of AFIS -- Chapter summary -- Review questions -- References -- Section 2: Fingerprint Processing: -- Introduction To Processing Methods: -- Key Terms -- Learning Objectives: -- Matrices and substrates -- Fingerprint development -- Health and safety -- General approach to evidence processing -- DNA -- Chapter summary -- Review questions -- References -- Forensic Light Sources: -- Key Terms -- Learning Objectives: -- Visual examination -- Physics of light -- Fluorescence and phosphorescence -- Lasers and ultraviolet imaging system -- Reflective ultraviolet imaging systems -- Chapter summary -- Review questions -- References -- Physical Processing Methods: -- Key Terms -- Learning Objectives: -- Fingerprint powder -- Compositions of fingerprint powders -- Fingerprint powder processing -- Varieties of fingerprint powders -- Chapter summary -- Review questions -- References -- Chemical Processing Methods: Porous Substrates: -- Key Terms -- Learning Objectives: -- Porous substrates -- Sequential processing -- Historical chemical reagents -- Ninhydrin -- DFO -- Indanedione -- Physical developer -- I Had A Case: Operation pendennis -- Chapter summary -- Review questions -- References -- Chemical Processing Methods: Nonporous Substrates: -- Key Terms -- Learning Objectives: -- Nonporous substrates -- Sequential processing -- Cyanoacrylate ester: superglue fuming -- Cyanoacrylate dye stains -- Vacuum metal deposition -- Semi-porous substrates -- Chapter summary -- Review questions -- References -- Chemical Processing Methods: Other Substrates And Matrices: -- Key Terms -- Learning Objectives: -- Other surfaces -- Oily fingerprints and greasy surfaces -- Bloody fingerprints -- Fingerprints on metallic surfaces -- Fingerprints on skin -- Fingerprints on adhesive surfaces -- I Had A Case: Janitor in the drum -- Chapter summary -- Review questions -- References -- Section 3: Fingerprint Analysis: -- Documentation: -- Key Terms -- Learning Objectives: -- Documentation -- Laboratory notes and forms -- Photography -- Evidence photography -- Photographic lighting techniques -- Common problems with photography -- Uploading and storing photos -- Final reports -- I Had A Case: Missiles in the Israeli desert -- Chapter summary -- Review questions -- References -- Crime Scene Processing: -- Key Terms -- Learning Objectives: -- Crime scene investigation -- Crime scene kit -- Processing the crime scene -- Modus operandi -- Categories Of Crime Settings: Burglaries -- Categories Of Crime Settings: Commercial scenes -- Categories Of Crime Settings: Vehicles -- Fingerprints and DNA -- I Had A Case: Point of entry -- Chapter summary -- Review questions -- References -- Fingerprint Comparisons: -- Key Terms -- Learning Objectives: -- Fingerprint comparisons -- Level 1,2, and 3 detail -- ACE-V -- Analysis -- Comparison -- Evaluation -- Verification -- How many points? -- Chapter summary -- Review questions -- References -- Palm Print Comparisons: -- Key Terms -- Learning Objectives: -- Palm print comparisons -- Anatomical areas and major creases of the palm -- Interdigital area -- Hypothenar area -- Thenar area -- Finger-joints -- Chapter summary -- Review questions -- References -- Courtroom Testimony: -- Key Terms -- Learning Objectives: -- Expert witness -- Judicial system -- Testimony is teaching -- Qualifying questions -- Direct examination -- Cross examination -- Preparing for court -- Day of court -- Daubert trilogy -- I Had A Case: Assassination of President John F Kennedy -- Chapter summary -- Review questions -- References -- Appendix A: Sequential processing -- Appendix B: Latent print reagent formulations and processes -- Appendix C: Expert witness testimony of Sebastian F Latona, FBI latent fingerprint examiner -- Index.
Includes bibliographical references and index.
Keywords: Fingerprints; Fingerprints -- Identification; Forensic sciences; Criminal investigation